KONTRIBUSI PENGETAHUAN AWAL (PRIOR KNOWLEDGE) DAN KETAHANMALANGAN (ADVERSITY QUATION) TERHADAP HASIL BELAJAR BK MAHASISWA S1 BIMBINGAN DAN KONSELING IKIP PGRI BALI - Juliawan, W.; Bawa, P. Wayan; Wiguna, D.G.E Sastra (LP2M IKIP PGRI Bali, 2019)
This study aims to determine: (1) the contribution of initial knowledge to the BK learning outcomes of Undergraduate Guidance and Counseling students, (2) the contribution of resistance to the BK learning outcomes of S1 Guidance and Counseling students, and (3) the contribution of initial knowledge and resistance to the learning outcomes of BK Undergraduate Guidance and Counseling students. This research is a correlational study. This research was conducted in the Department of Guidance and Counseling S1 IKIP PGRI BALI. The samples in this study were 75 people, sampling was done using simple random sampling techniques. Data collection methods in the form of tests and questionnaires using a Likert scale. The data analysis method used is multiple regression. The results showed that (1) initial knowledge contributed to the BK learning outcomes of Undergraduate Guidance and Counseling students (r = 0.61; p <0.05 and t = 6.59; p <0.05). (2) unresponsiveness contributes to the BK learning outcomes of Undergraduate Guidance and Counseling students (r = 0.90; p <0.05 and t = 18.83; p <0.05)). (3) The initial knowledge and disadvantage contribute to the BK learning outcomes of Undergraduate Guidance and Counseling students (r = 0.92; p <0.05 and F = 204; p <0.05) and have an effective contribution of 85%.